An increasing electromechanical window is a predictive marker of ventricular fibrillation in anesthetized rabbit with ischemic heart - Vudhiporn Limprasutr (2018)
© 2018 Japanese Association for Laboratory Animal Science. The QTc interval is widely used in Safety Pharmacological studies to predict arrhythmia risk, and the electromechanical window (EMW) and short-term variability of QT intervals (STV QT ) have been studied as new biomarkers for drug-induced Torsades de Pointes (TdP). However, the use of EMW and STV QT to predict ventricular fibrillation (VF) has not been elucidated. This study aimed to evaluate EMW and STV QT to predict VF in anesthetized rabbit model of VF. VF was induced by ligation of the left anterior descending and a descending branch of the left circumflex coronary arteries in a sample population of rabbits (n=18). VF was developed 55.6% (10/18). In rabbit with VF, the EMW was significantly higher than in rabbits without VF (96.3 ± 15.6 ms and 49.5 ± 5.6 ms, respectively, P < 0.05). STV QT had significantly increased before the onset of VF in rabbits that experienced VF, but not in rabbits that did not experience VF (11.7 ± 1.8 ms and 3.7 ± 0.4 ms, respectively, P < 0.05). The EMW and STV QT had better predictive power for VF with higher sensitivity and specificity than the QTc measure. The result suggested that the increasing of EMW, as well as the elevation of STV QT , can potentially be used as biomarkers for predicting of VF.